2019
DOI: 10.2174/1381612825666190116124233
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous Vegetables as Antioxidative, Chemopreventive and Antineoplasic Functional Foods: Preclinical and Clinical Evidences of Sulforaphane Against Prostate Cancers

Abstract: Background: Sulforaphane (SF, 1-isothiocyanato-4-(methyl-sulfinyl)-butane) is found in broccoli, cabbage and cauliflower. Methods: we performed a critical review on the antioxidative, chemopreventive and antitumor effects of SF from cruciferous vegetables against prostate cancers and molecular pathways. For a complete and reliable review, primary and secondary resources were used, including original and review articles, books and government documents published until March 2018. Articles that are in duplici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Additionally, the involvement of SFN in the progression of prostate cancer has been studied. The data obtained showed that the inhibition of the deacetylation of histones is driven by SFN [ 70 , 71 ]. Not only preclinical studies but also studies in humans showed that, by taking SFN, a reduction in prostate cancer incidence and progression could be obtained [ 72 , 73 ].…”
Section: Plant-derived Sulfur Compounds—gsls and Oscsmentioning
confidence: 99%
“…Additionally, the involvement of SFN in the progression of prostate cancer has been studied. The data obtained showed that the inhibition of the deacetylation of histones is driven by SFN [ 70 , 71 ]. Not only preclinical studies but also studies in humans showed that, by taking SFN, a reduction in prostate cancer incidence and progression could be obtained [ 72 , 73 ].…”
Section: Plant-derived Sulfur Compounds—gsls and Oscsmentioning
confidence: 99%
“…Alterations in the acetylation patterns of histones are a characteristic feature in PCa progression [34]. SFN has been shown to interfere with a key androgen receptor (AR) chaperone, Hsp90, by inhibition of histone deacetylase (HDAC) enzymes, which remove acetyl groups from histones, inhibiting HDAC activity within cancer cell lines [35]. SFN has been shown to directly attenuate the AR pathways present in the LNCaP PCa cell line via the inhibition of HDAC6 activity [36].…”
Section: Sulfur-containing Bioactives From Cruciferous and Alliacementioning
confidence: 99%
“…On the contrary, a higher intake of fresh, non-processed vegetables has been frequently associated with lower risks of some cancers such as breast [ 15 , 22 ] and colorectal [ 23 , 24 ] cancer and generally of cancers of the digestive tract [ 25 ]. Some in vitro studies have found that some compounds in some vegetables such as isothiocyanates (sulforaphane, glucoraphanin) and flavonoids (anthocyanidins, flavones, flavones) protect against the risk of carcinogenesis [ 23 , 26 , 27 ], consistent with these studies.…”
Section: Introductionmentioning
confidence: 99%